Breast Feeding and Weaning Practices in Thar Desert of Rajasthan, India - Singh, Madhu B; Lakshminarayan, J (Annals of Arid Zone, 2016)
Breast Feeding and Weaning Practices have a major effect on short term and long term nutritional status of infants. An attempt was made to find out the pattern of infant feeding practices in Thar Desert of Rajasthan so as to know the community perceptions existing in this area. Data were collected from 434 young women belonging to rural house-holds of Thar Desert. Analysis revealed that exclusive breast feeding rate (<4 months of age) was 0.09 indicating that majority of the mothers were discarding colostrum and delivering some fluids to their children. Predominant breast feeding rate was 0.90. Timely complementary feeding rate (6-9 months of age-groups) was 0.23. In present study, mean duration of breast feeding was 26 months. Continued breast feeding rate (1 & 2 year) was 0.95 and 0.59, respectively, indicating a ‘traditional face’ according to WHO typology. In studied population, majority of the mothers were illiterate, socio-economically backward and very particular about their cultural beliefs and practices. The study revealed that it is the mother’s perceptions and cultural beliefs, which determine the foods to be delivered to the child. So while planning community based educational intervention programs and to make them more effective and acceptable to the community, one has to keep these findings in mind regarding determination of the particular types of foods which are useful and culturally accepted. These programs should aim at correcting the local perceptions regarding feeding pattern by encouraging and improving the useful dietary pattern and discouraging the harmful ones. Key words: Breast feeding, weaning, desert, practices, traditions.